The internationalization of SMEs: an integrative approach - Korsakienė, Renata; Tvaronavičienė, Manuela (Journal of Business Economics and Management, 2012)
Presented paper aims to compare internationalization of Lithuanian and Norwegian SMEs by exploring the main motives and barriers restricting internationalization process. The authors strive to reveal the patterns of internationalization taking into account the aspects of main theoretical models. The research is based on the main ideas of stage, network and international entrepreneurship approaches. The main motives and barriers restricting internationalization process are based on the previous studies. In order to compare internationalization patterns of Lithuanian and Norwegian SMEs, quantitative research has been performed. The quantitative research is based on responses to a questionnaire embracing various aspects of internationalization. The sample of 300 SMEs was selected taking into consideration previous research. The survey allows concluding that Lithuanian SMEs emphasise geographic proximity as the most important criteria for international market selection. On the other hand, Norwegian SMEs perceive variables of international entrepreneurship theory as the important contributory factors in internationalization process. The authors conclude that Lithuanian SMEs rely on exporting; meanwhile Norwegian SMEs choose subcontracting/licensing or own representative abroad. Hence, Norwegian SMEs are seen at the more advanced stage of internationalization. Authors of the research have elaborated proposals, which are useful for further development of Lithuanian SMEs and take into consideration experience of Norwegian SMEs. The presented paper will contribute to the International Entrepreneurship Forum by providing new insights into further development of SMEs of Lithuania and Norway taking into consideration opportunities and threats.